Rustam khan - Hasan akbar kamal (Ferozsons (Pvt) Limited ; Lahore)
"Rustam Khan" is a powerful narrative that showcases the heroic journey of its protagonist, Rustam Khan, whose bravery, wisdom, and moral integrity shape him into a legendary figure in the face of adversity and challenges.